SOCIOGRAPHIC STUDY OF CAREER INTERESTS OF HIGH SCHOOL STUDENTS IN BAUBAU CITY, SOUTHEAST SULAWESI - Wijaya, Rasman Sastra (Universitas Pendidikan Indonesia, 2024)
One of the aspects that influence the emergence of students' career interests to make a career choice in a particular profession or job because of ethnic origin, social interaction, kinship which is considered good by the local community where an individual grows and develops. Some of the student's choices can be part of the purpose of life that leads to the tendency of a career profession because it reflects the conditions of the area he occupies. This study aims to obtain an overview of students' interests in terms of sociographic conditions of ethnic origin and gender. This study uses a quantitative approach with two-way Anova test inferential statistics. Data collection uses an interest scale to reveal the tendency of students' interest based on ethnicity, regional origin and kinship. The number of respondents is 803 and the sample is 10% or 83 people consisting of the Butonese, Bugis, Javanese, Wakatobi and Balinese. The results of this study show several findings and the influence of socio-economic conditions of student interest on the suitability of personality type and work environment based on the theory of interest in Holland that they choose.